Code-Switching, Critical Pedagogy, and Religious Identity: Insights from Indonesian Islamic Boarding School Classrooms - Assiddiqi, Muhammad Hasbi; Rahmi, Rahmi (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2025)
This study analyzes code-switching practices in pesantren classrooms, with a focus on Pesantren Darul Ulum in West Sumatra, and examines their pedagogical role in integrating religious values with academic subjects. A qualitative classroom ethnography was conducted, drawing on participatory and non-participatory observations across twelve lessons, in-depth interviews with teachers and students, and document analysis. Data were examined using thematic coding informed by sociolinguistic and critical pedagogy perspectives, with source and method triangulation employed to ensure validity. Findings reveal that code-switching between Indonesian, Arabic (Qur’anic verses, hadiths, religious terminology), and Minangkabau operates not only as a communicative tool but also as a pedagogical and ideological practice. Teachers strategically employ code-switching to connect modern academic knowledge with Islamic values, reinforcing students’ religious identities while fostering critical literacy. These insights challenge conventional views that position code-switching merely as pragmatic communication, highlighting instead its function as a medium of religiously grounded critical pedagogy. The novelty of this study lies in shifting the focus of code-switching research from pragmatic communication toward pedagogical, ideological, and identity-related dimensions within Islamic education. It offers a conceptual framework for understanding code-switching as an integrative tool bridging national curricula with religious values, thereby contributing to sociolinguistics, education, and the study of critical religious pedagogy.